Scientific production of the Geology and Mining Faculty of Higher Institute of Mining and Metallurgy, Cuba, in period 2003-2015 - Ortiz Núñez, Roelvis (2021)
The purpose of the research was to describe the scientific production of the Geology and Mining School of the Higher Institute of Mining and Metallurgy of Moa (Cuba), in scientific journals during 2003-2015 period. The study is developed by means of a research strategy that combines exploratory techniques of information search and quantitative analyses, through the documentary analysis and descriptive statistics. In this sense analyzed the scientific production for years, teaching departments, authors, and journals. A total of 224 publications were surveyed, of those 80 in scientific journals, through of the identification of the thematic focuses of research, the information given in the curriculum vitae and the databases queries. The results show the evolution and impact of the scientific production in the twelve years of the period under study. It concluded that, despite the number of registered publications in scientific journals is small, there is a matching between the scientific production and the established lines of investigation by the institution. These results reflect the interests and active areas of this Faculty, so the results can be an indicator of his evolution in the institution.